História de vida e efeitos do fogo em espécies de leiothrix (eriocaulaceae) com diferentes estratégias de propagação, na Serra do Cipó, MG - Ana Carolina de Oliveira Neves (2012)
In this work we compared life history traits and the effects of fire over four sympatric and congeneric Eriocaulaceae species representing three disctinct reproductive strategies. The species used as models and their propagation strategies were: Leiothrix crassifolia (rhizomatous seedproducing - RS), L. spiralis (pseudoviviparous rooted - PR), L. arrecta and L. propinqua (pseudoviviparous canopy-forming - PCF). We tested the central hypothesis that species with distinct reproductive strategies have different responses to the ecological questions investigated. The ultimate goal was to provide subsidies for in situ conservation and management of Eriocaulaceae species in face of an apparent increase in the fire frequency in rupestriand grasslands. Experiments were performed in a sandstone grassland area at Serra do Cipo, Minas Gerais State, and in laboratory to investigate aspects related to reproductive investment and pollination. In addition, we investigated L. arrecta life history in areas with distinct burning histories. Finally, we proceeded a literature review on the effects of fire in Eriocaulaceae aiming to suggest management actions to species inhabiting the Cerrado. It was observed that PCF species presented equivalent or higher reproductive allocation and reproductive effort than RS species. This was an unexpected result according to literature, in which PCF species are described as having a limited seed set. It was also observed that Leiothrix studied species are entomophilous, just like Comanthera (Eriocaulaceae). However, L. arrecta presents a combination of entomophily and agamospermy that was described for the first time in this family. Such a result is consistent with its life history that is deeply influenced by fire events that can eliminate pollinators for a time period. Leiothrix arrecta a pirophytic species has death, recruitment and growth cycles stimulated by fire. A review of scientific literature reveals that, on the one hand, frequent fires can lead Eriocaulaceae populations to decline through the exhaustion of seed bank and mortality (mainly seedlings), and stimulate reproduction and early death of adult individuals in monocarpic species. On the other hand, the exclusion of fire for long periods can lead to aging and decline of populations due to reduced recruitment and competition with herbaceous vegetation. PCF species are extremely affected by fire events because they occur in habitats with tall vegetation cover, dense populations being completely eliminated by fire. However, such species respond to burning with high elasticity by means of massive seedling recruitment. Longer time intervals (> 15 years) are needed to complete population growht. Populations of RS and PR species seem to be more resistent to fire than PCF species, because they inhabit areas with less inflamable, low vegetation cover, and recruit by seeds and also by rhizomes